Papel da O-Glicosilação com N-Acetil-Glucosamina nas alterações vasculares modulada pela ERK 1/2 via Interleucina-10 - Miguez, Jéssica Silva Gonçalves (2017)
O-Glycosylation with N-acetyl-glucosamine (O-GlcNAc) is defined as a post-translational modification that acts on several signaling pathways, among which we have proteins with important role in vascular function. On the other hand, several authors have demonstrated that the absence of interleukin-10 (IL-10) may favor vascular dysfunction. The objective of this study was to verify if O-GlcNAc promotes alteration in vasoconstriction by kinase modulators regulated by extracellular signals (ERK 1/2) via IL-10. For this, aorta of male C57BL / 6 mice (12 weeks) were incubated with Thiamet G (1 μM for 24 hours - selective OGA inhibitor capable of increasing overall levels of O-GlcNAc). Knockout mice for IL-10 (IL-10 -/-: B6.129P2- Il10tm1Cgn / J; 12 weeks) were also used. Vascular reactivity (n= 6) and western blot tests were performed to evaluate protein expression. The vessels of IL-10 -/- mice show a greater vasoconstriction for phenylephrine when compared to the control [Emax (% KCl) = 203.6 ± 8.39 vs 163.0 ± 10.64] and the same can be observed (Emax (% KCl) = 167.9 ± 3.46 vs. 126.1 ± 3.23), but incubation with an ERK 1/2 inhibitor prevented these effects (Emax (% KCl) = IL-10 -/- = 120.7 ± 5.40, Thiamet G = 144.2 ± 1.89). Western blot analysis revealed that IL-10 -/- mice showed an increase in ERK 1/2 expression (p = 0.0001), as well as vessels treated with Thiamet G (p = 0.0119), which also expressed more O-Glycosylated proteins (p = 0.0250). The OGT enzyme remained unchanged, whereas OGA expression was elevated (p = 0.0285). Regarding the IL-10 signaling pathway, it was observed that although the JAK1 enzyme is more expressed (p= 0.0287) in the vessels incubated with Thiamet G, STAT3 expression is decreased (p= 0.0048), which resulted in lower IL-10 tissue levels (p= 0.0001). These data suggest that increased OGlcNAc is able to increase ERK 1/2 activity and this effect is mediated by the decrease in the IL10 signaling pathway, which may result in vascular dysfunction.